2014
DOI: 10.2478/cipms-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition and variability of Hypericum perforatum L. from wild population in Kosovo

Abstract: Aerial parts of Hypericum perforatum L. (Hypericaceae) were collected from five wild populations in Kosovo, with aim to investigate the chemical composition and natural variation of essential oils between wild populations. This species could be considered of economic potential as it is widespread in Kosovo, on the other hand H. perforatum is one of the best-known medicinal herbs used in Kosovo folk medicine. Essential oils were obtained by steam distillation and analysed by GC-FID and GC-MS. Sixty-seven compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The studies of H. perforatum Table 1 CHEMICAL COMPOSITION OF THE H. PERFORATUM ESSENTIAL OIL populations originating from Greece [14] and Portugal [15], respectively, showed a higher content of alpha-pinene and beta-pinene than those reported in our study. The wild populations in Kosovo showed a high content of alphapinene along with other major components: 2methyloctane, beta-caryophyllene, germacrene D [12]. In contrast, a Serbian sample [10] showed a different chemical composition, in this study nonane (63.8%) being the most abundant component.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The studies of H. perforatum Table 1 CHEMICAL COMPOSITION OF THE H. PERFORATUM ESSENTIAL OIL populations originating from Greece [14] and Portugal [15], respectively, showed a higher content of alpha-pinene and beta-pinene than those reported in our study. The wild populations in Kosovo showed a high content of alphapinene along with other major components: 2methyloctane, beta-caryophyllene, germacrene D [12]. In contrast, a Serbian sample [10] showed a different chemical composition, in this study nonane (63.8%) being the most abundant component.…”
Section: Resultsmentioning
confidence: 57%
“…The extraction yield was 0.41% (v/w) based on the dry plant material. Comparatively, the contents of essential oils from Romania were 0.23% [6], Serbia 0.03-1.93 [25], Portugal 0.15% [15], Turkey 0.04-0.5% [26] and Kosovo 0.04-0.26% [12]. The H. perforatum EO's specific gravity at 25°C was 0.703±0.006 g/cm 3 ; the refractive index at 20°C was 1.431±0.041, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature data, large variation in EO content (0.04-1.93%) was also reported for plants from six different localities in Serbia [30]. Additionally, the yields of EOs from HP from Kosovo differed greatly depending on the population and ranged from 0.04 to 0.26% based on dry weight [31].…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, trans-(E)-caryophyllene and caryophyllene oxide were reported to be principal components. In the region of Kosovo, HP were characterized by the following main constituents: α-pinene (3.70-36.50%), 2-methyl-octane (1.10-15.50%), trans-(E)-caryophyllene (1.20-12.40%), caryophyllene oxide (3.30-17.70%) and n-tetradecanol (3.60-10.40%) [31].…”
Section: Chemical Composition (%) Of the Essential Oils From 11 Hypermentioning
confidence: 99%